Evaluating the Effectiveness of Customer Acquisition and Activation Strategies in Retail Securities: A Value-Added Analysis Approach - Ayuningtyas, Yulita Pratiwi; Hartanti, Dwi (Manunggal Halim Jaya, 2026)
This study evaluates the effectiveness of customer acquisition and activation strategies in retail securities services using a Value-Added Analysis (VA Analysis) approach. Adopting a qualitative case study methodology, the research focuses on PT X, a national securities firm in Indonesia, and investigates the efficiency of its onboarding process conducted through digital channels. Data were collected via semi-structured interviews with operational and marketing personnel, a netnographic review of customer feedback on social media, and internal document analysis. The onboarding activities were categorized into value-added, Business-value-added, and non-value-added activities to assess their contribution to customer activation. Findings indicate persistent inefficiencies, particularly in sales-driven product alignment and incentive distribution processes, which hinder conversion from account registration to initial transaction. The study suggests that improving key performance alignment, automating verification systems, and leveraging data analytics are crucial to transforming the onboarding process into a more value-generating system. This research contributes to the application of VA Analysis in evaluating service processes within digital financial ecosystems and offers practical insights for enhancing acquisition-to-activation effectiveness in competitive capital markets.